Perspectives, politics and prospects to combat the Coronavirus - Panja, Amrita (Asian Journal of Medical Sciences, 2021)
The Coronavirus disease (Covid-19) pandemic emerged in Wuhan, China during December 2019 and has spread all over the world. It has brought about huge threats to health and lives. The virus is highly contagious and it continuously evolves in the human population. The article is aimed to analyse the perspective, politics and probable prospects of Covid-19. It is further focused on possible challenges during the pandemic situation. Intensive research required in the field of virology to identify the probable potential drug invention for developing treatment strategies. This pandemic causes emotional, economic and social problems. Although the pandemic has some positive effects also. The article emphasizes the political and sociological aspects of the pandemic situation. Under the crisis, people have realised the value of caring, sharing, loving and helping the distressed ones instead of luxurious lifestyle. The pandemic has surely led to a new normal in our lives.